﻿A bug’s tale: revealing the history, biogeography and ecological patterns of 500 years of insect invasions - Daniela N. López; Eduardo Fuentes-Contreras; Cecilia Ruiz; Sandra Ide; Sergio A. Estay (NeoBiota, 2023)
The arrival of Europeans to the Americas triggered a massive exchange of organisms on a continental scale. This exchange was accelerated by the rapid increase in the movement of people and goods during the 20th century. In Chile, scientific and technical literature contains hundreds of records of non-native insect species established in different parts of the territory, from the hyperarid Atacama Desert to the Magallanes Region. Here, we analyse temporal trends, taxonomic diversity, biogeographic origin and main impacts of these species on different sectors in Chile from the European arrival to the present. Our task includes a review of old records in museum catalogues, libraries, collections, expedition records and catalogues. Almost 600 species of non-native insects have been reported to be established in Chile. Introductions started with the very arrival of Europeans to the central valley of Chile and underwent a huge acceleration in the second half of the 20th century. The order Hemiptera was the most prevalent amongst non-native insects. Most species are linked to agriculture and forestry. Species are of Palearctic origin in more than 50% of the records. In terms of temporal trends, the rate of established non-native species shows an abrupt increase at the beginning of the 1950s. This change may be associated with the strong development in agriculture and forestry in Chile after World War II and the increase in intercontinental air traffic. We believe that the understanding of past patterns of introductions is an important component in the design of current policies to minimise the impact of invasive insects.